Cybercrime and Its Countermeasures in the Indonesian Legal System - Zakiul Fuad; Mhd. Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
The rapid development of information technology has provided many conveniences in people's lives, but has also opened up opportunities for cybercrime, one of which is phishing. Phishing is a form of digital fraud by impersonating a trusted party to obtain sensitive information such as personal data and financial credentials. In Indonesia, the rise in phishing cases poses a serious threat to national digital security, especially with the low level of digital literacy in the community. This study aims to evaluate the effectiveness of the Electronic Information and Transactions Law (UU ITE) in dealing with phishing crimes and identify the main obstacles in its enforcement. The method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that normatively, the ITE Law contains several relevant articles to ensnare phishing perpetrators, such as Article 28 paragraph (1), Article 30, and Article 35. However, its effectiveness in practice is still limited due to the lack of an explicit definition of phishing, the difficulty of digital evidence, the weak capacity of law enforcement officers, and the lack of integration of handling mechanisms between agencies. Furthermore, the cross-border nature of phishing adds jurisdictional complexity and demands more intensive international cooperation. Therefore, legal reform is needed through the formulation of specific articles on phishing, strengthening the technical capacity of law enforcement agencies, and developing implementing regulations that support a swift and adaptive legal response to the dynamics of digital crime